SISTEM PENJAMINAN MUTU INTERNAL MANAJEMEN PENDIDIKAN TINGGI DI FAKULTAS VOKASI UNIVERSITAS AIRLANGGA SURABAYA - Imas Tita Anggraini; Detrianti Mutiara Hasan; Devianti Putri Prihartini; Nurviana Kummala Sari Zahrotun Nisa; Aurellia Salsabila Wynne Nissa (STKIP Pesisir Selatan, 2023)
The efforts of educational institutions to achieve their vision and mission are to implement a quality assurance system. This article discusses the implementation of Internal Quality Assurance Standards (SPMI) at the Vocational Faculty of Airlangga University. The main issues studied include the SPMI system/cycle, the role of students in SPMI, the obstacles experienced, the impact of SPMI implementation on learning success, as well as the process of evaluating and improving SPMI. This study uses a qualitative approach to gain a deep understanding of the observed phenomenon. Data was collected through in-depth interviews with lecturers, quality assurance unit staff, and academic administrative staff, as well as analysis of policy documents and procedures related to SPMI. The purpose of this study was to analyze the implementation of SPMI at the Vocational Faculty of Airlangga University, understand the role of students in SPMI, identify obstacles, and analyze the impact of SPMI implementation. The results of the study show that the implementation of SPMI at the Vocational Faculty of Airlangga University involves a structured cycle with clear stages. The role of students in SPMI provides input on the quality of learning and evaluation of lecturer performance. The obstacle faced was the lack of communication and coordination with the assessors. The impact of SPMI implementation on learning success includes improving the quality of learning, increasing student satisfaction, and increasing accreditation. The process of evaluating and improving SPMI is important for improving the quality of education. This article provides further contributions on the implementation of SPMI at the Vocational Faculty of Airlangga University.Â Keywords: Internal Quality Assurance Standards, Faculty of Vocational Studies, Airlangga University